The Influence of Learning Motivation and Discipline on Learning Achievement of Islamic Religious Education in State Elementary Schools - Amalia Fasya; Nefi Darmayanti; Junaidi Arsyad (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This study aims to determine the influence of learning motivation on PAI learning achievement, the influence of discipline on PAI learning achievement, and the influence of learning motivation and discipline on PAI learning achievement at SDN 101815 Sidodadi together. This type of research is quantitative, with a population of all classes IV, V, and VI totalling 177 learners and a sample of 66 learners. The data collection technique uses a questionnaire with a Likert scale, while the data analysis technique uses instrument tests, validity, and reliability tests. The hypothesis test uses multiple linear regression tests, t-tests, F tests, and efficiency determination. The results revealed that there was a positive and significant influence between learning motivation on PAI learning achievement of 6,076 > 1,999 and a sig value of 0.000 < 0.05, while the influence between discipline on PAI learning achievement was 6,659 > 1,999 and a sig value of 0.000 < 0.05. The influence between learning motivation and discipline on PAI learning achievement was jointly obtained by 41,657 > 3,140 with a sig value of 0.000 < 0.05 and a determination value of R 0.569 (56.9 %) means that 56.9% of PAI learning achievement is influenced by learning motivation and discipline factors. In comparison, 43.1% is influenced by other factors that were not studied in this study, such as family, environmental, economic, facility and other factors.